Air diffusion electrodes based on synthetized mesoporous carbon for application in amoxicillin degradation by electro-Fenton and solar photo electro-Fenton. (10th April 2018) - Garza-Campos, B.; Morales-Acosta, D.; Hernández-Ramírez, A.; Guzmán-Mar, J.L.; Hinojosa-Reyes, L.; Manríquez, J.; Ruiz-Ruiz, E.J.
Abstract: The aim of this work was to develop an air diffusion mesoporous carbon electrode (ADE-MC) as cathode for the in-situ electrogeneration of hydrogen peroxide and its application on electro-Fenton (EF) and solar photo electro-Fenton (SPEF) processes. Three different mesoporous carbon materials were obtained by organic-organic self-assembly synthesis (soft-template route) by changing concentrations of resorcinol-formaldehyde polymer as carbon precursor and Pluronic F-127™ surfactant as matrix-forming agent. The materials were characterized by X-ray diffraction (XRD), Raman spectroscopy, scanning electron microscopy (SEM), linear voltammetry (LV) and linear rotating disk electrode voltammetry (LV-RDE). MC materials showed pore diameter between 3.6 and 4.6 nm. The efficiency of ADE-MC was explored as a function of H2 O2 produced at current densities (50, 100 and 150 mA cm −2 ). The highest production of H2 O2 was 10.85 mmol L −1  by applying 150 mA cm −2 . Finally, the ADE-MC were used for the mineralization of amoxicillin (50 mg L −1 ), allowing complete degradation and mineralization percentages of 55% and 85% with EF and SPEF processes, respectively. MC electrodes produce H2 O2 in enough amounts that provide a viable option to degradation and mineralization of others organic pollutants in aqueous media by EF and SPEF processes.